2014
DOI: 10.1155/2014/692328
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of the Newly Designed Cementless Femoral Stem

Abstract: A morphology study was essential to the development of the cementless femoral stem because accurate dimensions for both the periosteal and endosteal canal ensure primary fixation stability for the stem, bone interface, and prevent stress shielding at the calcar region. This paper focused on a three-dimensional femoral model for Asian patients that applied preoperative planning and femoral stem design. We measured various femoral parameters such as the femoral head offset, collodiaphyseal angle, bowing angle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…This index was between 1.20 and 1.28 on the dogs of this study and this is also in the range already described by Palierne et al 2006 andPalierne et al 2008. On the other side, the variations of flare of proximal femoral canal on cranio-caudal direction require the designing of the anatomic femoral implants or other biologic fixation implants which are often used in human orthopedics (Baharuddin et al, 2014;Husman et al, 1997;Laine et al, 2000;Rubin et al, 1992;Yang et al, 2014). The cranio-caudal radiographs have been only used to calculate the CFI for dog femora (Ganz et al, 2010;Marcellin-Little et al, 1999;Palierne et al, 2006;Palierne et al, 2008;Pugliese, 2014;Rashmir-Raven and DeYoung, 1992).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This index was between 1.20 and 1.28 on the dogs of this study and this is also in the range already described by Palierne et al 2006 andPalierne et al 2008. On the other side, the variations of flare of proximal femoral canal on cranio-caudal direction require the designing of the anatomic femoral implants or other biologic fixation implants which are often used in human orthopedics (Baharuddin et al, 2014;Husman et al, 1997;Laine et al, 2000;Rubin et al, 1992;Yang et al, 2014). The cranio-caudal radiographs have been only used to calculate the CFI for dog femora (Ganz et al, 2010;Marcellin-Little et al, 1999;Palierne et al, 2006;Palierne et al, 2008;Pugliese, 2014;Rashmir-Raven and DeYoung, 1992).…”
Section: Discussionsupporting
confidence: 84%
“…Other side cortical thickness is an important factor to proper canal preparation (Peck and MarcellinLittle., 2013) In studies about THA, the cortico-medullary index is generally calculated only at the midshaft or at the ishtmus regions and at the medio-lateral direction (Baharuddin et al, 2014;Noble et al, 2003;Palierne et al, 2006;Palierne et al, 2008;Umer et al, 2010;Yeung et al, 2006). Femur has under the bending loadings in particularly.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of BMD to determine the quality of newly regenerated bones revealed that the tendency of BMD results was almost similar with that of BV/TV results. In analyzing the BMD using HU values, the threshold range of HU for soft tissue, cancellous bone, and cortical bone were ≈225, 226–661, and 662–1988 HU, respectively . At week 12, the HU of PCL/β‐TCP/Bone dECM scaffolds was significantly higher than that of other scaffolds.…”
Section: Resultsmentioning
confidence: 98%
“…Higher differences are also found on the endosteal widths at the metaphyseal region in human femur. 8,10,11 Andrade and colleagues calculated a lower CFI than the mean CFI of Palierne's studies. [19][20][21] And the variability in the body weights of dogs and the levels of endosteal width measurements was discussed.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4] The evaluation of canal flare is important since canal fill and stem fit is used to plan total hip arthroplasty. 1,[5][6][7][8][9][10][11] The concept of a canal flare index (CFI) was first defined by Noble and colleagues 6 to understand the proximal canal shape of the human femur using plain radiography. The diameter of the metaphyseal region in which the stem is placed proximally and the diameter of the isthmus where it is placed distally were used to calculate the CFI.…”
Section: Introductionmentioning
confidence: 99%